Zooplankton of the Paraguay River: A comparison between sections and hydrological phases - Frutos, Santa Margarita (2006)
Changes in the abundance, species richness and species diversity of zooplankton were studied in the Paraguay River. Fifty-nine sites were studied at two hydrological phases between Porto Cáceres (16°03'S-26°23'W) and the confluence with the Paraná (Argentine, 26°53'S-58°23'W), representing a distance of 2270 km. Zooplankton densities varied between 1 and 60 ind.l-1 at high water and between 11 and 100 ind.l-1 at low water. Multiple regression analysis revealed that the hydrological phase explained 64% of the variability in zooplankton density. Surveys found 196 taxa in the Paraguay River (including both the main course and its floodplain). The greater species richness was registered in the upper section. There were significant differences in the species richness and species diversity of Rotifera (Monogononta) between hydrological phases. In the main channel, the hydrological phase explained 54% of variability in species richness, whereas water temperature and electric conductivity explained less than 22% of the variability in species diversity. Rotifera was the most abundant group in both study periods. Despite the total number of species registered in the main channel, only six planktonic genera dominated the zooplankton assemblage (Polyarthra, Synchaeta, Filinia, Keratella and Lecane). The most abundant cladocerans belonged to Bosminidae (Bosminopsis sp.) and the dominant copepods were in the nauplii and juveniles stages. A longitudinal pattern in dominant taxa was not defined at high water. At low water, three species-site groups were separated in relation to environmental variables. The pulsing of the river determines the degree of connectivity with the floodplain and local features had a greater effect on zooplankton assemblages than large-scale landscape patterns.